(untitled) (Research, Society and Development, 2020)
Objective: To reveal the sociodemographic profile of Nursing students from a Public University in Rio de Janeiro, Brazil, regarding the variables Sex, Color / ethnicity / race were used; Age, Marital status, Presence of Offspring, Cohabitation and Responsible for family. Methods: It is a qualitative, exploratory-descriptive, field research, which is an excerpt of a doctoral thesis. For data analysis, simple and non-inferential statistics were used. The sample included 25 Nursing students from the fifth period. Results: The sociodemographic variables were tabulated in absolute and relative values ​​for a profile mapping of students. Conclusion: The findings of the present study allowed the mapping of the sociodemographic profile of the studied population, demonstrating the structure of the group, thus obtaining a fraction of the social identity of these students. The study evidenced that the profile of the participants is composed, for the most part, of young adults, female, single, without children, belonging to classes D and E who seek Nursing because of their affinity or desire for insertion in the health area.